SOME PROBLEMS OF OPTIMAL MANAGEMENT OF ECONOMIC SYSTEMS: SOME PROBLEMS OF OPTIMAL MANAGEMENT OF ECONOMIC SYSTEMS - Viktor, Oliynyk; Korsakova St, Rimskogo (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The task of optimal management of economic system is examined. Sulution of the problem comes true through the method of the Pontryagin maximum principle. As a function of the equation of state will use the Gross Domestic Product (GDP). An optimal management of state of financial system United Kingdom from initial position to the set end position is offered.